An introduction to statistical computing a simulation-based approach - Voss, Jochen (Wiley series in computational statistics, 2014)
This is a book about exploring random systems using computer simulation and thus, this book combines two different topic areas which have always fascinated me: the mathematical theory of probability and the art of programming computers.